PENGARUH CITRA MEREK, HARGA DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN MELALUI APLIKASI PENJUALAN ONLINE SHOPEE - Yoeliastuti Yoeliastuti; Evalina Darlin; Eko Sugiyanto (POLITEKNIK LP3I JAKARTA, 2021)
This study aims to determine the effect of brand image, price and promotion on people's purchasing decisions through the Shopee online sales application. The population taken in this research is all people who make purchases through the Shopee online sales application with a total of 104 respondents. Data collection techniques are primary data, namely distributing questionnaires via google form. In this study, it is also explained whether all elements are related, namely whether brand image, price and promotion have an effect on people's purchasing decisions through Shopee's online sales. This study is also to determine how much influence arises from brand image, price and promotion on people's purchasing decisions through Shopee online sales, it is hoped that the results obtained can be a reference or Shopee marketing strategy to increase sales. Based on the results of data processing carried out by simultaneous testing, it was found that there was an influence between promotion, brand image and price on consumer purchasing decisions through the Shopee online sales application by 38.2%.Keywords: Brand Image, Price, Promotion, Purchase Decision